Elephant interactive in wildlife tourism, Malaysia - Mohd, Abdullah; Daud, Darishawati; Hussin, Mohamed Zakaria (2010)
Human-wildlife interactive experience is highly sought out by people in wildlife tourism. Issues have cropped up to recognize the outcomes of human-wildlife contacts among visitors during the activities. A study was conducted based on visitors’ participation in the wildlife tourism in particular the elephant interactive program, level of interaction between both human and wildlife, and factors that have contributed to such relationships. A survey was conducted using structured questionnaire to 400 visitors in Kuala Gandah National Elephant Conservation Centre (KGNECC) in Pahang, a wildlife tourism site in Malaysia. The findings showed that respondents’ preferred the interactive activity when compared with non-interactive activities. It was found that tourists have sought the experiences such as bathing, feeding and riding with the elephants that involves direct contact or interaction with the animal. The level of interaction was identified as high when compared to passive or seeing activities, such as video show, taking pictures and watching elephants. Using factor analysis, the study showed that four factors dimensions contributed to human-wildlife interactive experience as outcomes, i.e. the animal interactive activities (Eigenvalue: 7.89), conservation-based activities (Eigenvalue: 5.032), environmentally educative (Eigenvalue: 3.830) and combination of programs (Eigenvalue: 2.803). Further analysis using Mann-Whitney Test and Kruskal-Wallis Test found that respondents’ demographic background have also influenced the generated factors of visiting KGNECC. Socio-demographic background such as visitors origin, age, marital status and education level have significant relationships with factors of visiting KGNECC. Wildlife tourism through interactive activities as the main attraction is therefore able to bring human and wildlife closer, and enabling them to immerse themselves in natural setting and the environmental elements.